2015
DOI: 10.2480/agrmet.d-14-00039
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal changes in nitrogen and potassium absorption rates of plants grown in a greenhouse

Abstract: In order to increase the efficiency of nutrient utilization in solution culture systems, it is indispensable to understand how plants absorb nutrients. A series of experiments were conducted using hydroponic culture system in the first to third experiments and soil culture system in the fourth experiment in a greenhouse in Okinawa, Japan. In the first experiment, changes in NO 3 -N absorption were measured every three hours during a 24-hour period on 40 days after transplanting (DAT) in cucumber. In the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Similarly, Okuyama et al. () found higher uptake rates of NO3 - during the day than during the night for rice. Matt et al.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Similarly, Okuyama et al. () found higher uptake rates of NO3 - during the day than during the night for rice. Matt et al.…”
Section: Discussionmentioning
confidence: 78%
“…In both soil culture and hydroponic experiments, Okuyama et al. () found that plants took up to 40% of the total N during the night regardless of cultivation systems, while Terabayashi et al. () reported that N and K uptake during the night ranged from 30–40% of the daily uptake, depending on season and temperature.…”
Section: Discussionmentioning
confidence: 99%
“…For the diurnal cycle reported in Okuyama et al (2015;Fig. 2a), cucumber nitrate uptake showed two peaks, one in the light and one in the dark.…”
Section: Observations Revealing Photosynthesis-independent Plant Root Nutrient Acquisitionmentioning
confidence: 90%
“…We identified 14 experiments (Table S1) that measured the diurnal cycle of plant root nutrient acquisition in crops. For example, Pan et al (1987) studied nitrate, potassium, and phosphate uptake by seedlings of five corn genotypes, and Okuyama et al (2015) observed nitrogen and potassium absorption by cucumber, komatsuna, tomato, and water spinach. Most experiments, except Okuyama et al (2015), collected measurements using artificial light conditions and nutrient solutions without soil, and we found no measurements of diurnal plant root acquisition of phosphate in soil.…”
Section: Observations Revealing Photosynthesis-independent Plant Root Nutrient Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation